THE USE OF MIND MAPPING ASSISTED PROBLEM BASED LEARNING MODEL ON STUDENT LEARNING OUTCOMES IN SUBSTANCE PRESSURE MATERIALS - Eka Sari Hutasoit; Ridwan Abdullah Sani; Siti Aisyah (UNIVERSITAS NEGERI MEDAN, 2022)
This research aims to find out whether there was variation in students' procedural knowledge, the effectiveness of learning using a problem-based learning model assisted by mind mapping in improving the quality of students' learning, and their response to the model used. The implementation is at SMP Negeri 17 Medan. The population was all collages students of class VIII. The process of grouping samples was performed by way of random sampling method. The instructions decided on as studies subjects were class VIII-5 and VIII-6 with 32 college students. The type of research used was Quasi Experiment with a two-group pretest-posttest design. The method used in the statistics series procedure was the more than one preference take a look at device with a total of 20 questions. Through the results of the study, the average of pre-test score for the experimental class was 36.87 and 36.25 for control class and the average of post-test experimental class was 76.71 and control class was 60.46. This showed that there was a difference in procedural information among students who were taught the use of a trouble-based studying version and students who were taught the usage of conventional gaining knowledge of methods. The magnitude of the increase was 63% for the experimental class and 37% for the control class. Both are in the medium category and it was concluded that the problem-based learning model was effectively applied in the science learning process. Student responses to the model were on positive criteria where their response to the problem-based learning process was quite high with an average size of 85.39%.